Challenges and prospects of linked data technology initiative in Bangladesh Libraries: A quantitative study - Nowrin, Shohana; Mostofa, Sk Mamun (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: The mission of libraries is to collect, organize, and make available various forms of information resources for potential users. Many libraries and historically significant institutions have rare and credible information resources that have little use because few people know they are available online. Purpose: The primary objective of this study is to ascertain the challenges and potential advantages associated with implementing Linked Data (LD) technology in libraries in Bangladesh. Method: A quantitative survey was conducted to collect data from the library professionals of some selected public university libraries in Bangladesh.. A total of 39 responded to the survey, which was usable among the 54 responses. The response rate was 72.2%. Once the quantitative data were collected, data were transferred into IBM®SPSS® statistics for analysis. Findings: The survey's results show that academic librarians are thoroughly aware of LD technology and believe they could have many advantages. Current research found that library professionals understand the challenges of adopting LD technologies in Bangladesh's libraries. Conclusion: This research is the first empirical investigation of the topic within the Bangladeshi setting that the authors are aware of. It shows how the information professionals in Bangladesh see the library LD and related initiatives and the possible advantages of putting it into action.